Toxicity Responses from Tributyltin Chloride on Haarder (Planiliza haematocheila) Livers: Oxidative Stress, Energy Metabolism Dysfunction, and Apoptosis - Changsheng Zhao; Anning Suo; Dewen Ding; Wencheng Song (Current Issues in Molecular Biology, 2025)
In coastal waters, tributyltin chloride (TBTC), a persistent organic pollutant, is extensively present. It is uncertain, therefore, if exposure to TBTC can harm haarders and how. This study exposed the fish for 60 days in order to investigate the molecular mechanism of haarder following TBTC poisoning. Our findings demonstrated that growth indices dropped, liver tissue was damaged, and the liver’s total tin concentration rose following TBTC exposure. Furthermore, we discovered that blood reactive oxygen species rose while total blood cell count decreased. As malondialdehyde levels rose, total antioxidant capacity and antioxidant enzyme activity (superoxide dismutase, catalase, and glutathione peroxidase) were markedly reduced. After being exposed to TBTC, liver cells displayed clear signs of apoptosis. Differentially expressed genes were primarily linked to oxidative stress, energy metabolism, and apoptosis, according to the transcriptome study of livers. Overall, the long-term stress of TBTC resulted in the antioxidant system being harmed, as well as serious malfunction of the energy metabolism and apoptotic response.